2013
DOI: 10.3390/ijerph10094012
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Tourists Regarding the Smoke-Free Policy at Suvarnabhumi International Airport, Bangkok, Thailand

Abstract: This study was conducted during February-March 2012 to determine the perception and support regarding smoke-free policy among tourists at Suvarnabhumi International Airport, Bangkok, Thailand. In this cross-sectional study, 200 tourists (n = 200) were enrolled by convenience sampling and interviewed by structured questionnaire. Descriptive statistics, chi-square, and multinomial logistic regression were adopted in the study. Results revealed that half (50%) of the tourists were current smokers and 55% had visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This might be because e-cigarettes have become easier to access, e.g., users can buy them through online platforms such as websites or social media, and e-cigarettes have quickly become the most popular tobacco product among the youth, mostly due to promotion and marketing efforts by e-cigarettes businesses [ 16 ]. Thailand Tobacco Products: Policy and Control Measures for Health in 2018 reported that Thai youth aged between 15 to 18 years old easily gained access to e-cigarettes via social media [ 17 ]. Furthermore, Kinnunen JM, et al studied 12,167 adolescents from 14 to 17 years old in Europe and showed that 34% of participants had tried e-cigarettes, and one of the associated factors of e-cigarettes smoking was low academic achievement [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be because e-cigarettes have become easier to access, e.g., users can buy them through online platforms such as websites or social media, and e-cigarettes have quickly become the most popular tobacco product among the youth, mostly due to promotion and marketing efforts by e-cigarettes businesses [ 16 ]. Thailand Tobacco Products: Policy and Control Measures for Health in 2018 reported that Thai youth aged between 15 to 18 years old easily gained access to e-cigarettes via social media [ 17 ]. Furthermore, Kinnunen JM, et al studied 12,167 adolescents from 14 to 17 years old in Europe and showed that 34% of participants had tried e-cigarettes, and one of the associated factors of e-cigarettes smoking was low academic achievement [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improved airport restrictions on smoking are necessary in order to reduce exposure to SHS in the U.S. and around the world. Increasing smoke-free policies in airports is not likely to be a deterrent to visitors, according to a recent survey of tourists in an international airport in Thailand [ 24 ]. The process of banning smoking in commercial airplanes was not simple and took nearly 40 years to be successfully implemented [ 1 , 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%